Analysis of the differentiation of peripheral B-lymphocytes in pregnant women with a habitual miscarriage - N. Yu. Sotnikova; A. I. Malyshkina; A. V. Kust; D. N. Voronin (Сибирский научный медицинский журнал, 2021)
The frequency of recurrent miscarriage among all desired pregnancies is 2-5 %. The important role of immune disorders in early termination of pregnancy has been proven. Elucidation of the nature of differentiation of B-lymphocytes in women with threatened miscarriage and habitual miscarriage in the anamnesis seems relevant, since it will clarify the immune mechanisms of the pathogenesis of this pathology. Aim of the study was to assess the nature of differentiation and type of the cytokine-producing function of peripheral B lymphocytes in women with a threatening spontaneous miscarriage and recurrent miscarriage in history.Material and methods. Pregnant women aged 18-40 years at a gestation period of 5-12 weeks were examined. The main group consisted of 60 pregnant women with a threatening spontaneous abortion at the time of the examination and a history of recurrent abortion. 35 pregnant women with uncomplicated pregnancy were examined as a control group. The comparison group consisted of 25 primary pregnant women with threatened spontaneous abortion at the time of the examination. The material for the study was peripheral venous blood. Subpopulations of B lymphocytes CD20+CD5+, CD20+CD5-, CD19+IgD+, CD20+IgM+, CD20+IgG+; CD19+CD20-CD38+, CD19+CD27-, CD19+CD27+, CD19+IgD+CD27+, CD19+IgD+CD27-, CD20+IL-4+, CD20+IL-6+, CD20+IL-10+ were determined by the method of flow cytometry.Results and discussion. In the main group, an increase in the proportion of B cells in the peripheral blood was recorded, mainly due to B2 lymphocytes, CD20 +IgM+ lymphocytes and memory cells, along with a decrease in the level of naive cells and plasma cells, as well as lymphocytes spontaneously expressing IL-6 and IL-10. Thus, the threatening habitual miscarriage is associated with a shift in B-lymphocyte differentiation towards immature forms. A decrease in the number of CD20+IL-10+ cells in patients of the main group can lead to a weakening of the suppressor associated with IL-10 and subsequent impairment of the maternal organism’s tolerance to a semi-allogeneic fetus. Similar changes in the differentiation and functional activity of B-lymphocytes were also observed with a threatening loss of the first pregnancy, which may indicate a single mechanism for the development of a threatening spontaneous miscarriage, the severity of which increases with repeated loss of pregnancy.